Performance properties optimization of triaxial ceramic-palm oil fuel ash by employing Taguchi design and flower pollination algorithm - Zainudin, Azlan (2018)
The combustion of wasted palm oil materials leads to the formation of Palm Oil Fuel Ash (POFA). The lack of use of POFA for beneficial applications causes environmental problems. The introduction of new raw material in an original composition can affect original optimal parameters. The excessive cost and time consumed is a main issue if high number of experiments need to be performed. Primarily, this research is about the optimization of triaxial ceramic employing the POFA process by the Taguchi design and Flower Pollination Algorithm (FPA). The recycled POFA was evaluated through the POFA layer formation method where selected POFA layers were employed as filler raw material. This research also provided the chronology of Taguchi design and FPA regarding the production of triaxial ceramic product. The research was then continued with the development of optimal parameters of the triaxial ceramic process containing POFA, specifically the following performance properties: shrinkage, water absorption, apparent porosity, bulk density, and flexural strength. Mainly, the Taguchi L18 orthogonal array was used as the design of experiment. Primarily, this research successfully attained the POFA layer formation for the triaxial ceramics. It was concluded that POFA could be successfully applied as filler material in triaxial ceramic application. Besides that, the Taguchi design and FPA were also successfully employed in this research field through the effectiveness of developed optimal design parameters. Taguchi Grey Relational Analysis (GRA) developed following optimal parameters: 15 wt.% of unground POFA, pressed at 2 t, and sintered at 1200 °C for 300 min of soaking time. In the meantime, both linear and interaction approach of FPA developed following optimal parameters: 5 wt.% of ground POFA, pressed at 4 t, and sintered at 1200 °C for 300 min of soaking time. It was successfully validated by the confirmation experiments including through crystalline phase and morphology analyses.